31.1 Davvisámegiella Norggas: ELDIA-prošeavtta dáhpáhusdutkamušraportta oaniduvvon veršuvdna - Marjomaa, Marko
Report on the case study on the North Sámi language in Norway, conducted within the EU-FP7 research project ELDIA. Abridged version in North Sámi.